Correlation of Dental Anomalies with Cleft Type and Gender in Non-Syndromic Oral Cleft Patients: A Cross-Sectional Study - YILMAZ, HANİFE NURAY (My University, 2022)
Objective To investigate the distribution of dental anomalies between non-syndromic orofacial cleft patients and their association with the cleft type and gender. Design Retrospective cross-sectional study involving examination of intraoral dental records and radiographs. Patients 300 non-syndromic orofacial cleft patients included (161 males and 139 females, mean age: 10.23 +/- 2.3 years). Main Outcome Measures: Variables analyzed: tooth agenesis, microdontia, and supernumerary teeth. Data analysis: Chi-square and Fisher\"s exact tests to investigate the correlation between dental anomalies, cleft type, and gender. Results Agenesis occurred in 66% of the subjects, supernumerary teeth in 19.6%, and microdontia in 18.3%. In females with unilateral left cleft lip and palate (CLP), agenesis was significantly higher compared to males. Both genders presented significant agenesis of maxillary lateral incisors and right central incisor. Significant agenesis of central incisor, canine and second premolar on the upper left side and lower second premolars were observed only in males, with significant microdontia for maxillary lateral incisors and left central incisor. Significant agenesis of maxillary first premolars was seen only in females. Agenesis in maxillary quadrants was significant for patients with unilateral right and left CLP, and bilateral CLP. In mandibular quadrants, agenesis was substantially higher for patients with isolated CP. Conclusions Results suggest that tooth agenesis and microdontia might not be directly associated with the cleft area\"s anatomical irregularity but are affected by gender and other genetic factors that regulate the development of the anomaly and the orofacial clefting mutually.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Diş Hekimliği; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Dentistry; Health Sciences; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Klinik Tıp; Klinik Tıp (MED); CERRAHİ; DENTISTRY, ORAL SURGERY & MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); SURGERY; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Cerrahi; Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Surgery